Autoconcepto Del Estudiante En Psicología: Una Perspectiva Multidimensional. - Peña Loaiza, Gerardo; Sánchez Padilla, Yadira; Carpio Mosquera, Carlos; Salamea Nieto, Rosa (Universidad Técnica de Machala, 2021)
The purpose of the present work was to evaluate the student's self-concept in psychology from a multidimensional perspective, by applying the AF-5 test (Self-concept Form 5) to a sample of 450 students from the careers of clinical psychology and psychopedagogy of the Technical University of Machala. A descriptive methodology of group difference was used, cross-sectional with a quantitative approach. The participants increased high levels of self-con-cept in the academic-work and physical dimensions, but not in the social and emotional dimensions. Some differences were found between the students of the lower and upper semesters, regarding the emotional dimension and only in the family dimension, significant differences related to sex and the career studied were revealed. In relation to age there were no significant differen-ces in any of the dimensions evaluated.
El presente trabajo tuvo como finalidad evaluar el autoconcepto del estudian-te en psicología desde una perspectiva multidimensional, mediante la aplicación del test AF-5 (Autoconcepto Forma 5) a una muestra de 450 estudian-tes de las carreras de Psicología Clínica y Psicopedagogía de la Universidad Técnica de Machala. Se utilizó una metodología descriptiva de diferencia de grupos, de corte transversal con enfoque cuantitativo. Los participantes pre-sentaron niveles altos de autoconcepto en las dimensiones académico-laboral y físico, no así en las dimensiones social y emocional. Se encontraron algunas diferencias entre los estudiantes de los semestres inferiores y superiores, en lo concerniente a la dimensión emocional y únicamente en la dimensión familiar se revelaron diferencias significativas relacionadas al sexo y a la carrera estudiada. En relación a la edad no hubo diferencias significativas en ninguna de las dimensiones evaluadas.
Keywords: AUTOCONCEPTO MULTIDIMENSIONAL; ESTUDIANTE UNIVERSITARIO; PSICOLOGÍA